Identification of a New Mutation p.P88L in Connexin 50 Associated with Dominant Congenital Cataract - Jin, Aixia; Zhao, Qingqing; Liu, Shuting; Jin, Zi-bing; Li, Shuyan; Xiang, Mengqing; Zeng, Mingbing; Jin, Kangxin (Frontiers in Cell and Developmental Biology, 2022)
Congenital hereditary cataract is genetically heterogeneous and the leading cause of visual impairment in children. Identification of hereditary causes is critical to genetic counselling and family planning. Here, we examined a four-generation Chinese pedigree with congenital dominant cataract and identified a new mutation in GJA8 via targeted exome sequencing. A heterozygous missense mutation c.263C>T, leading to a proline-to-Leucine conversion at the conserved residue 88 in the second transmembrane domain of human connexin 50 (Cx50), was identified in all patients but not in unaffected family members. Functional analyses of the mutation revealed that it disrupted the stability of Cx50 and had a deleterious effect on protein function. Indeed, the mutation compromised normal membrane permeability and gating of ions, and impeded cell migration when overexpressed. Together, our results expand the pathogenic mutation spectrum of Cx50 underlying congenital cataract and lend more support to clinical diagnosis and genetic counseling.